Can courage be a modern virtue? Seeking insight in Tocqueville, Mill, and Arendt - Berg, R (2018)
This dissertation examines the role of political virtues in modern contexts, and in particular, the role of courage as a potential modern political virtue. Despite frequent commentary on the importance of virtues, many political theorists have exhibited a strange reluctance to discuss the virtue of courage, at least in the sort of depth that it merits. This thesis puts forward the suggestion that courage is one of the most important modern political virtues and one ripe for rediscovery by political theorists and historians of political thought alike. Following the Ancient Greeks, the dissertation defines courage as the virtue which aids us in the proper assessment of threats and, where appropriate, the overcoming of fear in the service of causes we deem worthy, while emphasizing the contexts in which it is deployed. The dissertation also seeks to outline several reasons for the seemingly problematic relationship courage has with modernity, given its historical nexus with war and conquest, the striving for difference and distinction, and exclusionary notions of masculinity. The dissertation moves on to examine the role of courage in the thought of three thinkers—Tocqueville, Mill, and Arendt—all of whom have their doubts about the existence of courage in the modern world. Chapter 2 examines the role of courage in Tocqueville’s early modern America, swept up in Americans’ economic pursuits and captured by the soothing nature of consumer appetites. Chapter 3 examines the role of courage in Mill’s thought, arguing that Mill’s liberalism inherits many of the driving political and social concerns illuminated by Tocqueville, his friend and correspondent; however, Mill’s advocacy for a politics free from the crushing weight of inherited dogmas and traditions leads him to fall into the modern trap of jettisoning courage, even as his politics makes abundantly clear the need for it. Chapter 4 turns to Arendt’s skepticism that courage can ever exist in the modern world short of a fundamental act of recovery from the ancients, with a concomitant willingness to accept all of the problematic elements of courage as practiced by the Greeks. The dissertation concludes by stating that newer schools of thought on virtue, like liberal virtue theorists, have neglected the virtue of courage, which must be considered a modern political virtue, as there has been a proliferation of modern political contexts in which it is absolutely critical that we muster nothing short of courage. Courage is presented as a potential solution to the modern challenges facing liberalism from within, such as safe spaces, political correctness, no platforming, and trigger warnings, amongst others.